THE CENTRAL ROLE PLAYED BY ENTREPRENEURIAL MARKETING AND LEADERSHIP IN STARTUP GROWTH - Anmol (International Journal of Research -GRANTHAALAYAH, 2025)
This study explores the relationship between entrepreneurial marketing and leadership strategies with startup growth/success. It is quite evident as to how the business landscape has been evolving, tremendously with the advent of globalized technologies. Conventional business models stressed on available resources, state-sponsored advertisement, television time-slots and so on, to reach audiences and achieve lucrative success. Nowadays, several transitions have led to the evolution of leadership and entrepreneurial marketing strategies. Leaders tend to interpret marketing as an evolving process as well, one that is subject to change, fluidity and dynamics, much like the market itself. Which is why leaders stress on experimental ideas, digital resources and adaptability towards transitioning environments, with efforts to cope with the new nature of our business landscape. The goal of this paper is to explore the specifications and intricacies of (postmodern) entrepreneurial leadership and marketing strategies, viewing comprehensive theoretical frameworks and addressing the question: How does entrepreneurial marketing and leadership shape the trajectory of success regarding start-up companies? How effective are non-conventional business operations? We shall look at two examples/case studies to understand how these concepts apply to real-time events/companies, in an effort to arrive at substantial findings about the aforementioned themes.